2015
DOI: 10.4314/jasem.v19i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of <i>In-Situ</i> Natural Dendroremediation Capability of <i>Rhizophora racemosa</i> in a Heavy Metal Polluted Mangrove Forest, Rivers State, Nigeria

Abstract: Environmental pollution is assuming frightening dimensions in many parts of the world. This is not excluding Niger-Delta region of Nigeria where most of the country's oil and gas are sourced with attendant production of noxious substances as byproducts/residues/waste. Many of these noxious substances have been noted to be removable from polluted environment through proper application of phytoremediation techniques, particularly using native plant species. Consequently, this research was conceived to evaluate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
1
0
1
Order By: Relevance
“…Sediment content of heavy metals in May were Pb (0.2 -3.2 µg/g), Cd (0.001 -0.4 µg/g), Ni (<0.001 µg/g) while those in roots were Pb (0.04 -3.2 µg/g), Cd (0.2 -0.5 µg/g) and Ni (0.04 -0.7 µg/g). The values of Pb, Ni and Cd in sediments of this study also fall within the range reported by Gbosidom et al, (2017) but such values of metals observed in roots (current study) were well below those (Cd: 342.08 mgkg-1, Pb: 502.04 mgkg-1 and Pb 609.59 mgkg-1) reported by Erakhrumen (2015) in the root of other Mangrove plants in similar environments of the Niger Delta area. Age variation was not noticed during the month of May but metal accumulations were more in roots compared to sediments.…”
Section: Resultssupporting
confidence: 90%
“…Sediment content of heavy metals in May were Pb (0.2 -3.2 µg/g), Cd (0.001 -0.4 µg/g), Ni (<0.001 µg/g) while those in roots were Pb (0.04 -3.2 µg/g), Cd (0.2 -0.5 µg/g) and Ni (0.04 -0.7 µg/g). The values of Pb, Ni and Cd in sediments of this study also fall within the range reported by Gbosidom et al, (2017) but such values of metals observed in roots (current study) were well below those (Cd: 342.08 mgkg-1, Pb: 502.04 mgkg-1 and Pb 609.59 mgkg-1) reported by Erakhrumen (2015) in the root of other Mangrove plants in similar environments of the Niger Delta area. Age variation was not noticed during the month of May but metal accumulations were more in roots compared to sediments.…”
Section: Resultssupporting
confidence: 90%
“…Akumulasi logam pada sedimen mangrove ditentukan oleh beberapa faktor, antara lain laju sedimentasi dan laju penyerapan oleh tegakan. Beberapa penelitian menunjukkan bahwa tegakan mangrove secara aktif mengakumulasi logam berat dalam organ tanaman (Kathiresan et al, 2014;Pakzadtoochaei, 2013;Erakhrumen, 2015;Kamaruzzaman et al, 2009). Penelitian Kaewtubtim et al (2016) -0,305 -0,435 -0,300 -0,118 -0,305 -0,435 0,120 ± 0,382 x -0,094 ± 0,209 x 0,013 ± 0,299 p 2 m 0,402 -0,845 -0,063 -0,620 -0,063 -0,845 0,641 ± 0,224 x 0,226 ± 0,354 x 0,433 ± 0,349 q 3 m -0,375 -0,263 -0,255 -0,405 -0,375 -0,405 -0,043 ± 0,320 x -0,025 ± 0,373 x -0,034 ± 0,311 p (Rerata) -0,375 -0,845 -0,300 -0,620 0,269 ± 0,413 a 0,036 ± 0,313 a Keterangan : kelompok perlakuan yang ditandai dengan huruf yang sama menunjukkan tidak ada perbedaan yang signifikan pada taraf kepercayaan 95%…”
Section: Hasil Dan Pembahasanunclassified
“…This phenomenon/function is simply referred to as bioindication (Erakhrumen, 2014). Some plants, among these organisms, possess the ability to allow high concentrations of noxious/toxic substances in their tissues and/or participate in controlling them in the environment through processes collectively known as phytoremediation (Erakhrumen, 2007;Erakhrumen, 2015;Erakhrumen and Akhigbe, 2016). Apart from the earlier stated benefits derivable from different types of plants, there are others, such as the production of harvestable resources and participation of some plants in environmental stabilisation.…”
mentioning
confidence: 99%